Highly Flexible and Self‐Healable Zinc‐Ion Hybrid Supercapacitors Based on MWCNTs‐RGO Fibers. Issue 9 (29th July 2020) - Ni, Tong; Wang, Siliang; Shi, Junjie; Du, Xiaoyu; Cheng, Qinghua; Dong, Ziyan; Ruan, Limin; Zeng, Wei; Guo, Xiaohui; Ren, Xingang; Huang, Zhixiang
Abstract: As the flexible wearable devices are developing rapidly, the requirement for energy storage devices with high energy and power density, excellent flexibility, and high reliability is increasing. Fiber‐shaped supercapacitors offering high power density and excellent flexibility have attracted widespread attention. However, the low energy density and poor reliability limit the practical application of these fiber‐shaped supercapacitors. To overcome these problems, a new zinc‐ion hybrid fiber supercapacitor (ZHFSC) is designed and realized. As both capacitor‐type and battery‐type energy storage mechanisms can be used, the energy density of ZHFSC is expected to be improved. Furthermore, the excellent self‐healability of poly(vinyl alcohol) (PVA)/Zn(CF3 SO3 )2 aqueous gel electrolyte contributes to the high reliability of the ZHFSC. As a proof of concept, the maximum power density and energy density of the ZHFSC are, respectively, as high as 1433.2 mW cm −3 and 13.1 mWh cm −3, and the capacitance retention, respectively, has the high values of 87.8% and 70.5% under the bending degree of 150° and after the fifth self‐healing. This study offers an efficient method to realize the high‐performance supercapacitors for flexible wearable devices in the future. Abstract : A zinc‐ion hybrid fiber supercapacitor (ZHFSC) is realized based on multi‐walled carbon nanotubes‐reduced graphene oxide (MWCNTs‐RGO) fiber cathode, MWCNTs‐RGO‐Zn fiber anode, and poly(vinyl alcohol) (PVA)/Zn(CF3 SO3 )2 aqueous gel electrolyte. The ZHFSC exhibits the excellent flexibility and self‐healability: the capacitance retentions, respectively, retain the values of 87.8% and 70.5% under the bending degree of 150° and after the fifth self‐healing.